Synthesis and Studies of Glucosamine Conjugated BF2‐Oxasmaragdyrin. Issue 3 (17th January 2020) - Laxman, Kandala; Reddy, B. Pradeep K.; Robinson, Andrea; Srivastava, Rohit; Ravikanth, Mangalampalli
Abstract: A value addition to the existing NIR fluorescence imaging agents has been synthesized in the form of glucosamine conjugated BF2 ‐oxasmaragdyrin by treating meso ‐ p ‐carboxyphenyl BF2 ‐oxasmaragdyrin with 6‐amine‐6‐deoxy‐1‐ O ‐Boc‐2‐ N ‐Boc‐ β ‐D‐glucosamine in the presence of HBTU. The glucosamine conjugated BF2 ‐oxasmaragdyrin was thoroughly characterized by HRMS, 1D, and 2D NMR spectroscopy. The photophysical studies revealed that the conjugates are highly stable, absorb in visible‐ far‐red region (400‐700 nm) and emits in far‐red region (715 nm) with moderate quantum yields. The electrochemical studies showed that the molecules are stable under redox conditions with one reversible reduction and three reversible oxidations. The glucosamine conjugated BF2 ‐oxasmaragdyrin was found to be highly biocompatible with good cellular uptake in L929 and MDA‐MB‐231 cells. Abstract : A value addition to the existing NIR fluorescent molecules was synthesised in the form of glucosamine conjugated BF2 ‐Oxasmaragdyrin which was characterised by HRMS, 1D, 2D NMR, photophysical and electrochemical studies. The conjugate is highly biocompatible and internalised into the cytoplasm of L929 cells with excellent far‐red fluorescence which could be used for whole body imaging.